Lower‐resolution retrieval of scenes in older adults with subjective cognitive decline: Developing topics. (7th December 2020) - Ruiz‐Rizzo, Adriana L; Pruitt, Patrick J; Finke, Kathrin; Müller, Hermann J; Damoiseaux, Jessica S
Abstract: Background: Subjective cognitive decline (SCD) can predict the progression to mild cognitive impairment. Visual memory deficits in mildly impaired patients relate to decreased activity in brain regions beyond the medial temporal lobe, such as the parahippocampal place area (PPA). PPA's response to visual scenes is weaker in healthy older than younger adults but equally associated with memory recognition. PPA's response to scenes' perceptual details during encoding might support that association. Whether perceptual detail processing is reduced in SCD can help elucidate the disparity between perceived decline and normal performance. Here we test whether older adults with SCD ('SCD') use perceptual details to a lesser extent than older adults without SCD ('CON') and whether this is observed during the encoding or retrieval of a scene memory task. Methods: We measured BOLD‐fMRI activity in 37 healthy older adults (SCD: 16) during encoding, and calculated hit rate, false alarm rate, and total recognition accuracy during retrieval. We analyzed BOLD‐fMRI activity during scene encoding in PPA. PPA was defined based on a functional Neurosynth meta‐analysis of studies including the term "place" and further constrained to the lingual and posterior parahippocampal gyri, and posterior‐temporal and temporal‐occipital fusiform cortices. Scenes' perceptual details were quantified as the number of unique objects in it (high‐load: > 4; low‐load: < 4). Results: During encoding, PPA activity was higher for high‐load than low‐load scenes ( P = 2.08e‐06) but did not differ between SCD and CON ( P = .763), indicating comparable encoding of perceptual details across groups. Nevertheless, during retrieval, SCD appeared to benefit significantly less from perceptual details than CON ( P = .018), as their false alarm rates were similar for high‐ and low‐load scenes ( P = .879), whereas CON's were significantly lower for high‐load than low‐load scenes ( P = .002). Conclusions: Although tentative, our results suggest that SCD encode perceptual details similar to CON but use details to a lesser extent than CON when new information must be differentiated from old information during retrieval. Accordingly, memory complaints in SCD may reflect the perception of a 'lower‐resolution' retrieval, especially in the face of new information.